Mutational Profile of Homozygous β-Thalassemia in Rio de Janeiro, Brazil - Carrocini, Gisele C.S. [UNESP]; Venancio, Larissa P.R.; Pessoa, Viviani L.R.; Lobo, Clarisse L.C.; Bonini-Domingos, Claudia R. [UNESP] (Taylor & Francis, 2017)
β-Thalassemia (β-thal) is a hemolytic anemia that is caused by point mutations in most cases. The Brazilian population is highly heterogeneous and knowledge of the mutations that make up the genotypic profile of individuals can contribute information about the formation of the population and clinical condition of patients. In this study, we evaluated the mutations present in homozygous β-thal patients from Rio de Janeiro, Brazil. We analyzed 24 samples of peripheral blood of patients with homozygous β-thal. To identify the mutations, we carried out allele-specific-polymerase chain reaction (AS-PCR) and DNA sequencing. We found 11 different mutations on the β-globin gene. Among the most frequent mutations observed were HBB: c.92 + 6T>C, followed by HBB: c.93-21G>A, HBB: c.118C>T and HBB: c.92 + 1G>A. We also identified the rare mutation HBB: c.75T>A that was reported in an individual carrying Hb S (HBB: c.20A>T)/β-thal (HBB: c.75T>A) but not in Brazilian thalassemic patients, thus, this is the first report of this mutation in Brazilian β-thal patients. For its multiethnic character, Brazil has different mutations that cause β-thal and that are distributed with different frequencies according to the regions of the country. Our findings contribute to the description of the mutational profile of Brazilian thalassemic patients, showing wide heterogeneity and genetic variability.
Keywords: hemoglobin (Hb); hemolytic anemia; molecular genetics; mutations; β-Thalassemia (β-thal)